Using tropical forest ecosystem goods and services for planning climate change adaptation with implications for food security and poverty reduction - Nkem, J.; Santoso, H.; Murdiyarso, Daniel; Brockhaus, Maria; Kanninen, M. (2007)
Tropical forest ecosystems represent a common heritage with livelihood portfolios shared by a great majority of people especially in developing countries but are now threatened by climate change. In spite of their contribution to poverty alleviation and food security, and also for climate change responses (adaptation and mitigation especially through the market-incentive schemes (CDM) of the Kyoto Protocol) forests are still hardly integrated into national planning processes aimed at addressing any of these national development challenges. This is evident in some of the national documents of some developing countries such as the Poverty Reduction Strategy Paper (PRSP) to the World Bank, and the First National Communication to UNFCCC. This paper presents some preliminary outcomes of the Tropical Forests and Climate Change Adaptation (TroFCCA) project of the Center for International Forestry Research (CIFOR) whose overall mission is to underscore the importance of tropical forests for livelihood adaptation to climate change and mainstreaming adaptation into national development processes. The paper also highlights TroFCCA’s approach in engaging stakeholders from the onset in setting the agenda with the identification and prioritization of forest-based sectors as the entry point in the process of assessing the vulnerability to climate change and developing adaptation strategies for these selected development sectors. This is a highly crucial area with great policy implications. Planning with ecosystem goods and services seems to emerge as a prospective approach to demonstrate to policymakers the potential of forest ecosystems for livelihood adaptation to climate change which also enhances the opportunity for achieving food security and community resilience to poverty. TroFCCA’s approach in engaging stakeholders at the onset in defining their perception of ecosystem goods and services by virtue of their importance to household livelihoods and their contribution to national development emphasizes the significance of a place-based context in the valuation of ecosystem goods and services. This approach also contributes to raising public and policy awareness to climate change as part of the continuum of mainstreaming climate change adaptation into national development planning. The study also highlights the opportunities that an ecosystem approach provides for integrated natural resource planning for achieving co-benefits linked to the realization of two (1 and 7) important Millennium Development Goals. However, there are other policy and institutional reform challenges including governance, equity and rights to resources that need to be addressed in order to reap the full suite of benefits for climate change adaptation, poverty reduction and food security.